HELLP syndrome: Understanding and management of a pregnancy-specific disease. (May 2013) - Aloizos, S.; Seretis, C.; Liakos, N.; Aravosita, P.; Mystakelli, C.; Kanna, E.; Gourgiotis, S.
<x xml:space="preserve">Abstract</x> HELLP, a syndrome characterised by haemolysis, elevated liver enzymes and low platelets, a variant of pre-eclampsia/eclampsia, is a multisystemic disorder with an incidence of up to 0.9% in all pregnancies and occurs in about one-quarter of pre-eclamptic patients. Most obstetricians presume that HELLP derives from an autoimmune reaction, leading to a materno– fetal imbalance, with accompanying aggregation of platelets, endothelial malfunction along with inborn errors of fatty acid oxidative metabolism. HELLP is characterised by high mortality and morbidity rates, leading to possibly life-threatening complications regarding both the mother and the fetus. Delivery is indicated if HELLP syndrome occurs after 34 gestational weeks or the fetal and/or maternal conditions deteriorate. Vaginal delivery is preferable. Standard corticosteroid treatment is of uncertain clinical value in maternal HELLP syndrome. Future observations and research results may shed more light on improving our understanding of the aspects of HELLP syndrome.